Modelling a new ethical work climate framework for public sector auditors in Malaysia - Abdul Hamid, Fatima (2017)
The main objective of this paper is to investigate the ethical work climate (EWC) of the public sector auditors (PSA) in the National Audit Department (NAD), and to produce an EWC framework in relation to these auditors. In order to complete this framework, the antecedent of EWC, i.e. ethical culture was tested, as well as the outcomes of EWC, specifically code commitment, organizational commitment and work-related ethical behaviour. Survey questionnaires were distributed to the population of PSA in East and West Malaysia through a representative at each NAD office. The response rate was 66%. The findings of the OLS regressions confirmed that ethical culture is indeed an antecedent of EWC as well as its components. On the other hand, EWC and its components have a significant positive effect on all three outcomes, except for collective moral (CM) motivation. This component of EWC, CM motivation was only significantly positively associated with work-related ethical behaviour, but did not have any significant relationship with code commitment or organizational commitment. These findings are portrayed in an EWC framework and could be useful to the NAD as well as of interest to the public.